The relationship between financial sector deepening and income inequality in South Africa - Mandleni, Siyanda (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
This research analyzes the relationship between financial sector deepening and income inequality in South Africa from 1980 to 2019, using data from the World Bank Database and the Standardized World Income Inequality Database. An autoregressive distributed lag (ARDL) model is used to explore both the long- and short-run relationships that exist between these variables. Additionally, control variables like GDP, inflation, and structural changes that occurred, which include 1994 and 2005 are considered. According to the findings, the financial sector exacerbates income inequality in the long run. These findings highlight the need for policymakers to prioritize inclusive financial sector reforms. One recommendation is to enhance the access of Small, Medium, and Micro Enterprises (SMMEs) to formal financial services. For example, promoting more black industrialists and SMMEs in the supply of financial products and services. Possible reforms may include adjusting credit requirements for different income groups or offering lower interest rates on loans for businesses. Ensuring that more financial sector gains are retained within black communities can foster inclusive growth by generating jobs and ensuring a more equitable distribution of income.
Keywords: Financial services industry -- South Africa; Income distribution -- South Africa; Autoregression (Statistics); Small business -- South Africa; Business enterprises, Black -- South Africa